2009
DOI: 10.3766/jaaa.20.2.2
|View full text |Cite
|
Sign up to set email alerts
|

Subjective and Objective Evaluation of Noise Management Algorithms

Abstract: These results suggest that the directional microphone and the SII-based noise reduction algorithm may improve the SNR of the listening environments, and both the HINT and the ANL may be used to study their benefits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
61
3
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(76 citation statements)
references
References 19 publications
11
61
3
1
Order By: Relevance
“…It has been shown that a NR algorithm might be less effective when used in combination with a directional microphone. Peeters et al (2009) reported signifi cant improvement for a NR algorithm when used in combination with an omnidirectional microphone, but little or no improvement in combination with a directional microphone. In the present study the NR was only evaluated in combination with a directional microphone because the manufacturer recommends using this combination.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…It has been shown that a NR algorithm might be less effective when used in combination with a directional microphone. Peeters et al (2009) reported signifi cant improvement for a NR algorithm when used in combination with an omnidirectional microphone, but little or no improvement in combination with a directional microphone. In the present study the NR was only evaluated in combination with a directional microphone because the manufacturer recommends using this combination.…”
Section: Discussionmentioning
confidence: 95%
“…However, some studies have reported signifi cant improvements of specifi c NR algorithms on objectively measured speech recognition in noise. Peeters et al (2009) evaluated speech intelligibility in noise offered by a commercial HA using a fully adaptive directional microphone and a NR algorithm that performed gain reductions based on interactive calculation of the resulting speech intelligibility index (SII). Eighteen subjects with varying confi gurations of sensorineural hearing loss were fi t with binaural in-the-canal HAs (N ϭ 10) or open-fi t behind-the-ear HAs (N ϭ 8).…”
mentioning
confidence: 99%
“…Subtracting the BNL value from the MCL value yields the ANL measure that indicates a listeners' noise tolerance. It has been shown that the ANL measure is sensitive for perceptual effects of NRAs (Mueller, Weber, and Hornsby 2006;Peeters et al 2009;Pisa, Burk, and Galster 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Para isso, a maneira mais eficaz é minimizar a interferência do ruído ambiental na comunicação, com a utilização de microfones direcionais e algoritmos de redução de ruído 6,7 , presentes nesse dispositivo. Entretanto, nem sempre esses ajustes são suficientes para diminuir as queixas destes pacientes.…”
Section: Introductionunclassified